Reliability analysis of ballast cleaning device based on fuzzy FTA and FMEA. Issue 5 (January 2021) - Wang, J; Cui, Z X; Li, S D; Yang, T; Cheng, H Y; Na, R S
Abstract: On the basis of analyzing the fault tree diagram of the ballast cleaning device of railway switch ballast cleaning machine, the fuzzy fault tree of the ballast cleaning device is established by blurring the probability of bottom event. Introducing grey fuzzy analysis correlation method, using the normal fuzzy comprehensive evaluation method of combining the theory and experts, quantitative and qualitative analysis, the fuzzy fault tree based on fault tree's minimum cut sets, the fuzzy importance degree of the basic events, calculation of each failure mode and the top event correlation, figure out the influence of the top event to occur to the larger events and failure mode. Then FMEA method is used to analyze the key parts of ballast cleaning device such as gripper and sprocket, and corresponding compensation measures are put forward according to the specific failure reasons.